2006
DOI: 10.1164/rccm.200502-309oc
|View full text |Cite
|
Sign up to set email alerts
|

Limited Restoration of Cystic Fibrosis Lung EpitheliumIn Vivowith Adult Bone Marrow–derived Cells

Abstract: These results demonstrate that adult marrow cells can be recruited to airway epithelium and induced to express Cftr in mice otherwise lacking this protein. However, the number of observed chimeric epithelial cells is small and new strategies for enhancing airway epithelial remodeling by adult bone marrow-derived cells will be necessary for correction of defective CFTR-dependent chloride transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
162
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(180 citation statements)
references
References 47 publications
13
162
2
3
Order By: Relevance
“…The CFintoWT mice fared worse than WT mice, suggesting that hematopoietic BMDC may play a role in the excessive immune response of CF mice to P. aeruginosa infection. In this study, Ͻ1% of the epithelial cells in the lung were BMderived, which may be too low to justify the survival advantage in the WTintoCF mice (18).…”
Section: Discussionmentioning
confidence: 80%
“…The CFintoWT mice fared worse than WT mice, suggesting that hematopoietic BMDC may play a role in the excessive immune response of CF mice to P. aeruginosa infection. In this study, Ͻ1% of the epithelial cells in the lung were BMderived, which may be too low to justify the survival advantage in the WTintoCF mice (18).…”
Section: Discussionmentioning
confidence: 80%
“…However, as analytical techniques have improved, despite the earlier reports demonstrating substantial engraftment of lung epithelium with donor-derived cells, more recent reports demonstrate that only small numbers of transplanted adult marrowderived cells engraft in recipient lungs, particularly in airway or alveolar epithelium [19][20][21][22]. This includes only rare engraftment and CFTR expression in airway epithelium following transplantation of adult marrow-derived cells containing wildtype CFTR to CFTR KO mice [21] (Figure 2). Comparable low level engraftment was observed in intestinal epithelium of CFTR KO mice following transplant with wildtype marrow-derived cells [23].…”
Section: Lung Repair and Remodeling With Adult Bone Marrow-derived Stmentioning
confidence: 99%
“…As reviewed in that report, many of those studies were based on sex-mismatched transplantation and in situ demonstration of Y chromosome-containing donor marrow-derived cells in recipient lungs by fluorescence in situ hybridization (FISH), followed by immunohistochemical phenotyping of the donorderived cells [18]. However, as analytical techniques have improved, despite the earlier reports demonstrating substantial engraftment of lung epithelium with donor-derived cells, more recent reports demonstrate that only small numbers of transplanted adult marrowderived cells engraft in recipient lungs, particularly in airway or alveolar epithelium [19][20][21][22]. This includes only rare engraftment and CFTR expression in airway epithelium following transplantation of adult marrow-derived cells containing wildtype CFTR to CFTR KO mice [21] (Figure 2).…”
Section: Lung Repair and Remodeling With Adult Bone Marrow-derived Stmentioning
confidence: 99%
“…The authors declare that using bone marrow stem cells as a vector for gene delivery has several advantages, including their accessibility, their easily homing to the inflamed lung tissue via intratracheal injection or by migration after intravenous injecttion, the feasibility to be manipulated in vitro, and their low immunogenicity and high host compatibility [78]. MSCs carrying CFTR genes do well differentiate into lung epithelial cells and produce epithelial marker such as surface proteins [79]. A more recent study demonstrated that engraftment of BM-MSCs expressing keratinocyte growth factor (KGF) gene protects from bleomycin-induced pulmonary fibrosis in vivo [80].…”
Section: Maximizing the Effects Of Stem Cell Engraftmentmentioning
confidence: 99%